Generalized Virtually Stable Maps and Their Associated Sequences. (23rd June 2013) - Chaoha, P.; Iampiboonvatana, S.; Intrakul, J.
Abstract : We extend the concept of virtual stability of continuous self-maps to arbitrary selfmaps and investigate the structure of sequences associated with uniformly virtually stable selfmaps. We also obtain a necessary and sufficient condition for a uniformly virtually stable selfmap to have the largest possible associated sequence. Examples of a uniformly virtually stable selfmap having the prescribed largest sequence and a uniformly virtually stable selfmap having no largest sequence are given.